PERANCANGAN DESIGN UI/UX APLIKASI E-COMMERCE CALLANS COFFEE & EATERY - Juan Prima Bangun Priyadi (2023)
Callans Coffee & Eatery is a coffee shop engaged in the business of selling food and beverages. Coffee shop owners and several other stakeholders want to improve service to their customers by creating an application that will make it easier for their customers to place orders. Stakeholders believe that the front view that will interact directly with the user is important to make well so that the business process continues and can achieve the goals of the application. In this research, the problem to be solved is designing a good UI/UX design for the Callans Coffee & Eatery application. The limitation of this research is only to make prototypes of UI/UX designs that are ready to be developed into mobilebased applications. This study uses the Design Thinking method, with the main processes namely Emphatize, Define, Ideate, Prototype and Testing. By using the Design Thinking method, after successfully designing a UI/UX design for the Callans Coffee & Eatery application, the last step is to conduct testing with the System Usability Scale (SUS) questionnaire. The test results produce a final score of 87.17. Based on these results it can be concluded that the design created can be easily used and accepted by users